Adolescents\' Health: A qualitative study on Adolescents in Khorramabad - Sorror Parvizi; Fariba Sepahvand; Akram Sanagu; Naghmeh Razzaghi (Iran University of Medical Sciences, 2008)
Background and Aim: There are some reasons for doing qualitative researches: the importance of the health as a fundamental concept, the adolescence as an important period, lots of age-related special risk factors, and the uniqueness of adolescents in their perspectives to the society are some examples. The aim of this content analysis study was exploration of perspectives on health among adolescents of Lore ethnicity as an important Iranian ethnic minority.Materials and Methods: Twenty-five adolescents have been interviewed deeply and openly considering to ethical issues until data saturation. A Qualitative Content Analysis has been carried out for data analysis.Results: Content analysis on explanation of adolescents showed four categories: experiencing educational difficulties, the role of internalized religious beliefs in adolescents' health, economical problems, and social resources and supports. Adolescents pointed out on educational and socio-economical factors as well as the crucial role of religious behaviors and social participations. Some related factors for the sense of not being healthy were: the experience of discrimination, lack of educational facilities, motiveless teachers, exam stress, economical problems, exhausted busy parents, and lack of social facilities. Adolescents' health promotions are among priorities of national development program. Therefore, social facilities like job opportunities, cleaning society of cigarette, alcohol and addictive materials play a crucial role in adolescents' health from their points of view.Conclusion: Providing adolescents' health is the milestone of national development. Promotion of social services, especially job opportunities, controlling alcohol consumption and cigarette smoking and providing teaching can promote adolescents' health.